1985
DOI: 10.5358/hsj1972.11.2_46
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Size at Maturity of Female Hawksbill Turtles (<i>Eretmochelys imbricata</i>), with Speculations on Life-History Tactics Relative to Proper Stock Management

Abstract: The mean nesting sizes, and subsequent reproductive rates, of Arabian Peninsula hawksbill turtles (Eretmochelys imbricata) are significantly smaller than other hawksbill populations.These differences can not presently be explained due to the lack of basic life history information and, consequently, resource managers are unable to realistically manage any hawksbill population. Research, although costly and time consuming, must be initiated to obtain the demographic data needed; age at maturity, sex ratios, mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In the current study, the percentage of yolkless eggs, including very small eggs and odd-shaped eggs, ranged between 6 and 21% (Table 2), which was within the limits of previous study (Hirth, 1980). However, the clutch size of wild hawksbills ranged from 32-250 eggs, while the diameter of normal eggs ranged from 34-39.6 mm (Witzell and Banner, 1980;Limpus et al, 1983;Hirth et al, 1985;Witzell, 1985;Wood, 1986;Miller, 1997;Moncada et al, 1999;Pilcher and Ali, 1999;Xavier et al, 2006). In the current study, the clutch sizes produced by the hawksbills were relatively small; however, for eight of nine turtles, the clutch sizes (except Turtle no.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the current study, the percentage of yolkless eggs, including very small eggs and odd-shaped eggs, ranged between 6 and 21% (Table 2), which was within the limits of previous study (Hirth, 1980). However, the clutch size of wild hawksbills ranged from 32-250 eggs, while the diameter of normal eggs ranged from 34-39.6 mm (Witzell and Banner, 1980;Limpus et al, 1983;Hirth et al, 1985;Witzell, 1985;Wood, 1986;Miller, 1997;Moncada et al, 1999;Pilcher and Ali, 1999;Xavier et al, 2006). In the current study, the clutch sizes produced by the hawksbills were relatively small; however, for eight of nine turtles, the clutch sizes (except Turtle no.…”
Section: Discussionsupporting
confidence: 54%
“…3) were within the limits of previous studies (Table 2). Witzell (1985) reported that turtle body size and age correlate with clutch size in nesting hawksbill turtles. In our study, seven of the nine hawksbills were definitely virgins, because these turtles were bred in captivity (hatching in 1994).…”
Section: Discussionmentioning
confidence: 97%
“…Comparisons of the morphologies among populations provide a better understanding of evolutionary and genetic relationships, whereas comparisons of the body sizes among individuals and populations help to clarify physiological and ecological relationships. It has been reported that body size is connected to body temperature (Spotila and Standora 1985), metabolic rate (Prange and Jackson 1976), growth rate (Bjorndal and Bolten 1988), and clutch size (Witzell 1985). Because it is relatively easy to measure the morphological characteristics of marine turtles, there have been a number of studies of carapace size in various populations of the hawksbill turtle, Eretmochelys imbricata (Linnaeus, 1766) (Witzell 1985).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that body size is connected to body temperature (Spotila and Standora 1985), metabolic rate (Prange and Jackson 1976), growth rate (Bjorndal and Bolten 1988), and clutch size (Witzell 1985). Because it is relatively easy to measure the morphological characteristics of marine turtles, there have been a number of studies of carapace size in various populations of the hawksbill turtle, Eretmochelys imbricata (Linnaeus, 1766) (Witzell 1985). However, because of the difficulty of gathering specimens and determining the sex of immature turtles, these studies often had only a small sample size and hadn't dealt with the distinction between females and males.…”
Section: Introductionmentioning
confidence: 99%